Biocatalyic synthesis of unusually photoluminescent oligomers and electrically conducting polymers of 4‐(3‐pyrrolyl)butyric acid. Issue 21 (21st June 2014) - Bouldin, Ryan M.; Kokil, Akshay; Ponrathnam, Timothy; Urban, Nicholas; Kumar, Jayant; Samuelson, Lynne A.; Nagarajan, Ramaswamy
ABSTRACT Unusually photoluminescent undoped oligomers and doped electrically conducting polymers of 4‐(3‐Pyrrolyl)butyric acid have been enzymatically synthesized using the oxidoreductase soybean peroxidase as a catalyst. This biocatalytic approach provides a direct route to a fluorescent‐undoped oligomer of pyrrole that requires no protection/deprotection chemistry. The synthesis is carried out in aqueous media that requires only monomer, enzyme, and hydrogen peroxide. The undoped oligomer exhibits stable emission properties and is highly sensitive to the presence of environmentally important metal ions, such as Co(II), Hg(II), and Cu(II) in solution. Electrically conducting polymers can also be obtained by adding a dopant to a buffered reaction solution prior to initiating the polymerization. Polymers doped with camphor‐10‐sulfonic acid exhibit conductivity values as high as 10−2 S/cm. Additionally, polymers synthesized in the presence of a biobased cationic template, N, N, N‐trimethylchitosan chloride, exhibit conductivity values that are an order of magnitude greater than polymers synthesized with the anionic polymeric template, poly(styrene sulfonic acid)‐sodium salt. The biobased synthetic strategy described here is the first report of directly obtaining an undoped, fluorescent conjugated oligomer of a pyrrole in aqueous solution. Unlike conventional chemical catalysts, the enzyme does not dope the oligomer and therefore provides the opportunity to directly obtain fluorescent conjugated species. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 41035.